HUMAN DIGNITY, MORAL HARASSMENT AND JOB SATISFACTION - AN ANALYSIS OF ASPECTS INHERENT TO THE HEALTH OF PUBLIC SERVANTS (REMUNOM, 2025)
The 1988 Federal Constitution is a milestone in the consolidation of fundamental rights in Brazil, guaranteeing human dignity as a central principle. In the context of work, this protection is challenged by moral harassment, especially in the public service, characterized by repetitive practices that compromise the physical and psychological integrity of workers. This study, based on a literature review, analyzes the impact of moral harassment on the occupational health of public servants, identifies gaps in Brazilian legislation, relates moral harassment to job satisfaction, and highlights the need for preventive policies and organizational interventions that promote healthy and respectful environments. The conclusion is that comprehensive national regulations, associated with educational and cultural actions, are urgently needed to guarantee dignified and satisfactory working conditions.